Richness and composition of macrophyte assemblages in four Amazonian lakes - Roger Paulo Mormul (Acta Scientiarum. Biological Sciences, 2013)
Aquatic macrophytes are an important component in the structure of lakes in Neotropical floodplains, for example, because they support a high diversity of invertebrates and vertebrates. In this paper, we tested whether or not the variability of macrophyte assemblages is lower in spatially close quadrats than among quadrats of different lakes. The study was carried in four lakes in a large Amazonian floodplain (Purus river), where floating meadows were investigated. A total of 49 taxa of macrophytes were found. Five species dominated and three species were rare. Taxa richness, composition and beta diversity differed more between than within lakes. Because high beta diversity was found among the lakes, they should be considered individually important for maintaining the gamma diversity of macrophytes within the Purus River floodplain, and this should be considered in plans of lake management.